2018
DOI: 10.1111/1462-2920.14262
|View full text |Cite
|
Sign up to set email alerts
|

The path of electron transfer to nitrogenase in a phototrophic alpha‐proteobacterium

Abstract: The phototrophic alpha-proteobacterium, Rhodopseudomonas palustris, is a model for studies of regulatory and physiological parameters that control the activity of nitrogenase. This enzyme produces the energy-rich compound H , in addition to converting N gas to NH . Nitrogenase is an ATP-requiring enzyme that uses large amounts of reducing power, but the electron transfer pathway to nitrogenase in R. palustris was incompletely known. Here, we show that the ferredoxin, Fer1, is the primary but not sole electron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 44 publications
0
30
0
Order By: Relevance
“…During growth on succinate, our data are compatible with the classical view that excess H 2 production by the V‐Nase strain leads to slower growth compared with the Mo‐Nase utilizing strains. For example, it has a lower biomass N:C ratio despite a higher abundance of the primary electron donor to Nase, the ferredoxin protein Fer1 (log2 abundance difference of 0.53 ± 2.56 relative to the wild type strain, p < 0.01; Fixen et al ., ). These data indicate that, on succinate, nitrogen acquisition is more limiting to growth than electron balance.…”
Section: Resultsmentioning
confidence: 97%
“…During growth on succinate, our data are compatible with the classical view that excess H 2 production by the V‐Nase strain leads to slower growth compared with the Mo‐Nase utilizing strains. For example, it has a lower biomass N:C ratio despite a higher abundance of the primary electron donor to Nase, the ferredoxin protein Fer1 (log2 abundance difference of 0.53 ± 2.56 relative to the wild type strain, p < 0.01; Fixen et al ., ). These data indicate that, on succinate, nitrogen acquisition is more limiting to growth than electron balance.…”
Section: Resultsmentioning
confidence: 97%
“…1). The NADH generated can be used by R. palustris cells to reduce flavodoxin or ferredoxin, the direct electron donor of nitrogenase via the FixABCX enzyme complex (22,23). Therefore, organic acid-alcohol pairs are good candidate substrates to study how electron availability affects CH 4 and H 2 production.…”
Section: Discussionmentioning
confidence: 99%
“…This may point to the use of Flds as an adaptive strategy to fix N 2 in oxic environments. Moreover, under iron-deficient conditions that characterize most circumneutral oxic environments, diazotrophs tend to synthesize Flds preferentially as primary electron donors to Nif [92]. Studies have also shown that electron delivery by Fd or Fld can be complemented by other Fds or Flds that are encoded in the genomes of diazotrophs [70], [93], [94], [73], [95].…”
Section: Sources Of Reducing Equivalents During Aerobic and Anaerobicmentioning
confidence: 99%